Benign mixed tumour of the minor salivary gland - Madi Medhini; Bhat Supriya; Shetty Pushparaja; Madiyal Ananya; Babu Subhas G. (Medicinski fakultet i Klinika za stomatologiju, Niš, 2023)
Introduction: The most common major salivary gland neoplasm is the Pleomorphic adenoma. Only 10% of the pleomorphic adenoma occur in minor salivary glands. 42.8% to 68.8% of cases with intraoral lesion occurs in the palate. Here we present a rare case of a pleomorphic adenoma masquerading as a lesion of odontogenic origin. Case report presents a male patient who reported with a chief complaint of swelling in the upper left tooth region since 3 months. Panoramic radiograph revealed shadow of a soft tissue swelling in the left maxillary posterior region with destruction and resorption of the alveolar process. Radiographic differential diagnosis of benign odontogenic/non-odontogenic cysts or tumours, benign minor salivary gland tumours were considered. Excisional biopsy was carried out and the lesion was removed in total up to the periosteum and the overlying mucosa and sent for histopathologic examination, which suggested pleomorphic adenoma. Conclusion: Pleomorphic adenoma is a benign neoplasm which has excellent prognosis with a cure rate of more than 95%. However, periodic long term follow up is mandatory.